Hydrogen storage: Recent improvements and industrial perspectives. (16th March 2017) - Barthelemy, H.; Weber, M.; Barbier, F.
Abstract: Efficient storage of hydrogen is crucial for the success of hydrogen energy markets (early markets as well as transportation market). Hydrogen can be stored either as a compressed gas, a refrigerated liquefied gas, a cryo-compressed gas or in hydrides. This paper gives an overview of hydrogen storage technologies and details the specific issues and constraints related to the materials behaviour in hydrogen and conditions representative of hydrogen energy uses. It is indeed essential for the development of applications requiring long-term performance to have good understanding of long-term behaviour of the materials of the storage device and its components under operational loads.